The schedule of administration of canakinumab in cryopyrin associated periodic syndrome is driven by the phenotype severity rather than the age - Caorsi, Roberta (BioMed Central, 2013)
INTRODUCTION: Interleukin-1 (IL-1) blockade is the treatment of choice of cryopyrin associated periodic syndromes (CAPS). Anti-IL-1 monoclonal antibody (canakinumab) was recently registered. However no clear data are available on the optimal schedule of administration of this drug. The aim of the present study was to analyse the impact of canakinumab on CAPS patients in daily clinical practice and to identify the best schedule of administration according to age and phenotype. METHODS: 13 CAPS patients (10 children and 3 young adults) treated with canakinumab were followed for 12 months. Clinical and laboratory parameters were collected at each visit. Health-related quality of life (HRQoL) was recorded at month 12. Complete response was defined as absence of clinical manifestations and normal examinations. Clinical and laboratory variables at last follow-up were compared with those registered at the moment of anakinra discontinuation. RESULTS: seven patients with chronic infantile neurological cutaneous articular (CINCA) syndrome, four patients with Muckle-Wells syndrome (MWS) and two patients with an overlapping MWS/CINCA phenotype were analysed. CINCA patients experienced a higher number of modifications of the treatment (increased dosage or decreased dosing interval) in respect to MWS patients. At the end of the follow-up CINCA patients displayed a higher frequency of administration with a median dose of 3.7 mg/kg (2.1 mg/kg for MWS patients). Canakinumab was withdrawn in a patient with CINCA for incomplete response and poor compliance. The effect of canakinumab on HRQoL was similar to that observed during treatment with anakinra, with the exception of an improvement of the psychosocial concepts after the introduction of canakinumab. CONCLUSIONS: The use of canakinumab in daily practice is associated with persistent satisfactory control of disease activity but needs progressive dose adjustments in more severe patients. The clinical phenotype, rather than the age, represents the main variable able to determine the need of more frequent administrations of the drug at higher dosage.